Promovendo a alfabetização científica, a interdisciplinaridade e o protagonismo estudantil no ensino médio por meio da bioquímica em um livro interativo digital - Dazzi, Bruna Jejesky (2024)
Biochemistry is an interdisciplinary science that combines at least two major areas of scientific knowledge: Biology and Chemistry. Teaching Biochemistry in high school is challenging for both teachers and students, requiring the use of different methodological approaches. This includes, for example, interdisciplinary experiments with the encouragement of investigative strategies, contributing to facilitate the teaching-learning process of students. In this sense, this Master’s Thesis (TCM) presents a Digital Interactive Book (DIB), “The scientist girl in: the cell and the biomolecules - a digital book for the teaching of biochemistry by investigation”. It tells the story of a girl named Ana who collects mysterious particles in her backyard, generated by an explosion, and identifies them with the help of her teacher. Fourteen experiments are developed over fifteen chapters, presented in experimental investigative scripts that work with Biochemistry content in an interactive and interdisciplinary way. The material was designed to be used by Biology and Chemistry teachers with high school students and can be easily adapted for science teachers to use in elementary school. The tool has the potential to develop interdisciplinary teaching through Biochemistry, based on the proposition of hypotheses and the use of Experimental Investigative Scripts. In addition, the TCM presents to teachers a model of an elective discipline entitled “Scientific Literacy” placed in an Instruction Guide as a Supplement to the DIB, with a suggestion of using the scripts in a sequential and structured way. Also, the product pays tribute to pioneering women scientists in Brazil through the characters that refer to their surnames, reinforcing the important female presence in science. Finally, the didactic resource of this TCM aims at the construction and understanding of scientific thinking by developing scientific literacy, interacting Chemistry and Biology through Biochemistry, placing students of different levels as protagonists in the teaching-learning process